Accounting in cloud - Jana Singerová (European Financial and Accounting Journal, 2018)
Cloud computing is a new technological trend that since the last decade brings challenges in computed accounting, such as a significant reduction of running cost, together with unrestricted access to data from anywhere and anytime. Cloud accounting software enables its users a real time access to business finances, easy set up and easy use, access to information from anywhere, work with sales force, to synchronize instantly with bank, make tax returns precise and effortless. Cloud computing offers a short implementation time and low initial costs and it is offered by ERP providers in the SaaS (Software as a Service) mode. As an essential condition for massive expansion is generally considered availability of access to the high frequency internet. As accounting data are very valuable, security, such as encryption of data, granting access to the data and backups are necessary conditions to ensure their proper treatment. The aim of this article is to identify key advantages and disadvantages and milestones of such a solution.
Keywords: M15; M41; 650; Accounting information systems; Cloud accounting; ERP; Integration